A Comparison of Automated Perfusion- and Manual Diffusion-Based Human Regulatory T Cell Expansion and Functionality Using a Soluble Activator Complex. (25th May 2020) - Jones, Mark; Nankervis, Brian; Roballo, Kelly Santos; Pham, Huong; Bushman, Jared; Coeshott, Claire
Absence or reduced frequency of human regulatory T cells (Tregs) can limit the control of inflammatory responses, autoimmunity, and the success of transplant engraftment. Clinical studies indicate that use of Tregs as immunotherapeutics would require billions of cells per dose. The Quantum® Cell Expansion System (Quantum system) is a hollow-fiber bioreactor that has previously been used to grow billions of functional T cells in a short timeframe, 8–9 d. Here we evaluated expansion of selected Tregs in the Quantum system using a soluble activator to compare the effects of automated perfusion with manual diffusion-based culture in flasks. Treg CD4 + CD25 + cells from three healthy donors, isolated via column-free immunomagnetic negative/positive selection, were grown under static conditions and subsequently seeded into Quantum system bioreactors and into T225 control flasks in an identical culture volume of PRIME-XV XSFM medium with interleukin-2, for a 9-d expansion using a soluble anti-CD3/CD28/CD2 monoclonal antibody activator complex. Treg harvests from three parallel expansions produced a mean of 3.95 × 10 8 (range 1.92 × 10 8 to 5.58 × 10 8 ) Tregs in flasks (mean viability 71.3%) versus 7.00 × 10 9 (range 3.57 × 10 9 to 13.00 × 10 9 ) Tregs in the Quantum system (mean viability 91.8%), demonstrating a mean 17.7-fold increase in Treg yield for the Quantum system over that obtained in flasks. The two culture processes gave rise to cells with a memory Treg CD4 + CD25 + FoxP3 + CD45RO + phenotype of 93.7% for flasks versus 97.7% for the Quantum system. Tregs from the Quantum system demonstrated an 8-fold greater interleukin-10 stimulation index than cells from flask culture following restimulation. Quantum system–expanded Tregs proliferated, maintained their antigenic phenotype, and suppressed effector immune cells after cryopreservation. We conclude that an automated perfusion bioreactor can support the scale-up expansion of functional Tregs more efficiently than diffusion-based flask culture.